Squences Of Service Implementation In Improving The Service Quality At Lobby Lounge Bar And Restaurant JW Marriot Hotel Surabaya - Wibawa, I Ketut; Mathilda, Kezia (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2023)
The purpose of this study was to analyze the implementation of the Sequence of Service and the impact of implementing the Sequence of Service in improving service quality at the Lobby Lounge & Bar Restaurant JW Marriott Hotel Surabaya. This research is qualitative research with data collection through observation, documentation, and interviews. Data were analyzed using descriptive analysis method with reference to the Sequence of Service theory and Service Quality theory. The implementation of the Sequence of Service carried out at the Lobby Lounge Bar & Restaurant consists of, namely Greet and Show Interest in the Guest, Take Cocktail Orders, Order and Deliver Drinks, Service at the table, Tabletop Maintenance & Guest Service, and the last is Close Open Checks & Farewell. It shows that the Implementation of Sequence of Service can improve the Quality of Service at the Lobby Lounge Bar & Restaurant. The impact of implementing the Sequence of Service can have a positive or negative impact. The positive impact is that guests will be satisfied and provide positive feedback/reviews for the services provided. The negative impact is that guests feel dissatisfied with the services provided and have an impact on service quality, guest reviews, and restaurant ratings.